Cybersecurity Laws: Protecting Personal Data in the Age of Digital Transformation - Syamsul Bahri; Pong Krit; Siri Lek (Rechtsnormen: Journal of Law, 2026)
Background. The rapid acceleration of global digital transformation has fundamentally reorganized the socio-economic landscape, rendering personal data highly vulnerable to sophisticated cyber threats and systemic exploitation. Purpose. This research aims to critically evaluate the efficacy of contemporary cybersecurity laws in safeguarding individual privacy amidst this hyper-connected environment. Method. The investigation adopts a qualitative legal research design, utilizing a comparative analysis of data protection regimes across diverse jurisdictions through a specialized techno-legal analytical framework. Results. Findings indicate a significant regulatory disclosure paradox, where stringent legislation increases transparency and reporting rates without immediately reducing the absolute frequency of data breaches. The data suggests that technical alignment within statutory language is more critical for legal efficiency than the severity of financial penalties. This study concludes that the future of data sovereignty depends on the seamless integration of legal principles into the software development lifecycle. Conclusion. Legislators must move toward agile, principle-based frameworks that account for the borderless nature of digital networks and emerging technological complexities. Robust legal infrastructures are essential not only for privacy but as a primary pillar of national economic security and public trust.